Evaluasi Tingkat Ketidakrataan Jalan Nasional Papua Barat Dengan Menggunakan Alat Roughometer III: Studi Kasus: Ruas Jalan Dalam Kota Manokwari - Rinto Gultom; Indra Birawaputra; Radinal Bakri (Universitas Papua, 2023)
Road is one of the important and influential transportation infrastructures for the development of an area. This development will affect the volume of traffic which will put an increasing load on the pavement so that this has an impact on the functional decline of the road. The functional management of the road becomes a measure in the assessment which becomes a reference for determining the type of evaluation program that must be carried out, one of which is road roughness. In this study, the evaluation of the level of road leveling using the International roughness index (IRI) method as an indicator in the assessment ofan roads produced from the Roughometer III tool. Evaluation is carried out to determine the unevenness of road sections and road handling carried out for the level of road damage. From the calculation results, it is known that the condition of the level of equality on the ruas of the Yos Sudarso Manokwari road L line (left), 76.53% Good, 23.47% Fair, and R lane (right), 4.69% Excellent, 67.14% Good, 23.47% Fair, 4.69 % Poor . For ruas road Trikora Wosi Manokwari line L (left), 58.63% Good, 41.37%, and line R (right), 3.66% Excellent, 74.35% Good, 18.32% Fair, 3.66% Poo. On the Drs. Esau Sesa Manokwari road section L line (left), 3.66% Excellent, 7.68% Good, 63.97% Fair, 25.79% Poor 2.56% Bad and R lane (right), 13.00% Good , 76.77% Fair , 10.24% Poor